EDC News Letter - Osman, Wail Nuri; Miskeen, Elhadi Ibrahim (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 2 (2014), 2014)
The production of health professionals in particular physicians in the required numbers and of adequate quality is essential for any well performing health system. It is estimated that more than three hundreds colleges, faculties or schools of medicine are operating in the 22 Member States in the Eastern Mediterranean Region (EMR). In recent years, there has been a substantial increase in the number of medical schools, which has led to significant expansion in the medical workforce in the EMR. The physician population density rose significantly from the year 1990 to the year 2013 with the exception of Group 3 countries.